Extended-criteria donors in liver transplantation Part II: reviewing the impact of extended-criteria donors on the complications and outcomes of liver transplantation. (2nd July 2016) - Nemes, Balázs; Gámán, György; Polak, Wojciech G.; Gelley, Fanni; Hara, Takanobu; Ono, Shinichiro; Baimakhanov, Zhassulan; Piros, Laszlo; Eguchi, Susumu
ABSTRACT: Extended-criteria donors (ECDs) have an impact on early allograft dysfunction (EAD), biliary complications, relapse of hepatitis C virus (HCV), and survivals. Early allograft dysfunction was frequently seen in grafts with moderate and severe steatosis. Donors after cardiac death (DCD) have been associated with higher rates of graft failure and biliary complications compared to donors after brain death. Extended warm ischemia, reperfusion injury and endothelial activation trigger a cascade, leading to microvascular thrombosis, resulting in biliary necrosis, cholangitis, and graft failure. The risk of HCV recurrence increased by donor age, and associated with using moderately and severely steatotic grafts. With the administration of protease inhibitors sustained virological response was achieved in majority of the patients. Donor risk index and EC donor scores (DS) are reported to be useful, to assess the outcome. The 1-year survival rates were 87% and 40% respectively, for donors with a DS of 0 and 3. Graft survival was excellent up to a DS of 2, however a DS >2 should be avoided in higher-risk recipients. The 1, 3 and 5-year survival of DCD recipients was comparable to optimal donors. However ECDs had minor survival means of 85%, 78.6%, and 72.3%. The graft survival of split liver transplantation (SLT) was comparable to that of whole liver orthotopic liver transplantation. SLT was not regarded as an ECD factor in the MELD era any more. Full-right-full-left split liver transplantation has a significant advantage to extend the high quality donor pool. Hypothermic oxygenated machine perfusion can be applied clinically in DCD liver grafts. Feasibility and safety were confirmed. Reperfusion injury was also rare in machine perfused DCD livers.